Keterdedahan Dan Pemanfaatan Informasi Oleh Petani Sayuran - Syatir .; Djuara P. Lubis; Krishnarini Matindas (Jurnal Komunikasi Pembangunan, 2013)
ABSTRACT Agricultural development growns toward modern agriculture along with the development in science and technology in the field of agricultural technology and management, supported by fast development of communication technology. In current agricultural communities, information has become a significant part of their farming activities, because information actually plays a crucial role in improving the effectiveness and efficiency of the farming process, supporting decision-making process, and triggering innovation. The objectives of this study were (1) to describe vegetable farmers’ exposure to sources of information; (2) to analyze the relationship between the characteristics of farmers and exposure to information sources; and (3) to learn the relationship between exposure to information sources and the utilization of information. The study was designed as a descriptive-correlational survey research and it was conducted in Tugu Selatan village, Cisarua subdistrict, Bogor regency. The data was collected by means of simple random sampling and the data analysis used Spearman rank. The research result  showed that the farmers got the most varied materials from extension officers and farmer groups. Meanwhile, the highest use of information was enlightening. There was a significant correlation between variables of age, experience, land area, and types of vegetables and several other variables such as exposure to information sources. Some variables of exposure to information sources were significantly correlated with the use of information. Keywords: exposure to information sources, information utilization, vegetable farmers